Gesture-based Graph-theoretic Robot Formation Control - Sajid, Mahroo (2022)
A Master of Science thesis in Mechatronics Engineering by Mahroo Sajid entitled, “Gesture-based Graph-theoretic Robot Formation Control”, submitted in June 2022. Thesis advisor is Dr. Shayok Mukhopadhyay. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).